ANS complex of St John's wort PR‐10 protein with 28 copies in the asymmetric unit: a fiendish combination of pseudosymmetry with tetartohedral twinning. (1st April 2015) - Sliwiak, Joanna; Dauter, Zbigniew; Kowiel, Marcin; McCoy, Airlie J.; Read, Randy J.; Jaskolski, Mariusz
<x xml:space="preserve">Abstract</x> Hyp‐1, a pathogenesis‐related class 10 (PR‐10) protein from St John's wort (Hypericum perforatum), was crystallized in complex with the fluorescent probe 8‐anilino‐1‐naphthalene sulfonate (ANS). The highly pseudosymmetric crystal has 28 unique protein molecules arranged in columns with sevenfold translational noncrystallographic symmetry (tNCS) along c and modulated X‐ray diffraction with intensity crests at l = 7n and l = 7n± 3. The translational NCS is combined with pseudotetragonal rotational NCS. The crystal was a perfect tetartohedral twin, although detection of twinning was severely hindered by the pseudosymmetry. The structure determined at 2.4 Å resolution reveals that the Hyp‐1 molecules (packed as β‐sheet dimers) have three novel ligand‐binding sites (two internal and one in a surface pocket), which was confirmed by solution studies. In addition to 60 Hyp‐1‐docked ligands, there are 29 interstitial ANS molecules distributed in a pattern that violates the arrangement of the protein molecules and is likely to be the generator of the structural modulation. In particular, whenever the stacked Hyp‐1 molecules are found closer together there is an ANS molecule bridging them.